Disability and Care Needs Among Older Americans - FREEDMAN, VICKI A.; SPILLMAN, BRENDA C. (The Milbank quarterly, 2014)
Context: The cost of late-life dependency is projected to grow rapidly as the number of older adults in the United States increases in the coming decades. To provide a context for framing relevant policy discussions, we investigated activity limitations and assistance, care resources, and unmet need for a national sample of older adults. Methods: We analyzed the 2011 National Health and Aging Trends Study, a new national panel study of more than 8,000 Medicare enrollees. Findings: Nearly one-half of older adults, or 18 million people, had difficulty or received help in the last month with daily activities. Altogether, 1 in 4 older adults receiving help lived in either a supportive care (15%) or a nursing home (10%) setting. Nearly 3 million received assistance with 3 or more self-care or mobility activities in settings other than nursing homes, and a disproportionate share of persons at this level had low incomes. Nearly all older adults in settings other than nursing homes had at least 1 potential informal care network member (family or household member or close friend), and the average number of network members was 4. Levels of informal assistance, primarily from family caregivers, were substantial for older adults receiving help in the community (164 hours/month) and living in supportive care settings (50 hours/month). Nearly all of those getting help received informal care, and about 3 in 10 received paid care. Of those who had difficulty or received help in settings other than nursing homes, 32% had an adverse consequence in the last month related to an unmet need; for community residents with a paid caregiver, the figure was nearly 60%. Conclusions: The older population—especially those with few economic resources—has substantial late-life care needs. Policies to improve long-term services and supports and reduce unmet need could benefit both older adults and those who care for them.